The Diagnostic Performance of the Richmond Agitation Sedation Scale for Detecting Delirium in Older Emergency Department Patients - Han, Jin H. (Acad Emerg Med, 2015)
OBJECTIVES: Delirium is frequently missed in older emergency department (ED) patients. Brief (<2 minutes) delirium assessments have been validated for the ED, but some ED health care providers may consider them to be cumbersome. The Richmond Agitation Sedation Scale (RASS) is an observational scale that quantifies level of consciousness and takes less than 10 seconds to perform. The authors sought to explore the diagnostic accuracy of the RASS for delirium in older ED patients. METHODS: This was a preplanned analysis of a prospective observational study designed to validate brief delirium assessments for the ED. The study was conducted at an academic ED and enrolled patients who were 65 years or older. Patients who were non-English speaking, deaf, blind, comatose, or had end-stage dementia were excluded. A research assistant (RA) and a physician performed the RASS at the time of enrollment. Within 3 hours, a consultation-liaison psychiatrist performed his or her comprehensive reference standard assessment for delirium using Diagnostic and Statistical Manual of Mental Disorders Fourth Edition, Text Revision (DSM-IV-TR) criteria. Sensitivities, specificities, and likelihood ratios with their 95% confidence intervals (CIs) were calculated. RESULTS: Of 406 enrolled patients, 50 (12.3%) had delirium diagnosed by the consult-liaison psychiatrist reference rater. When performed by the RA, a RASS other than 0 (RASS > 0 or < 0) was 84.0% sensitive (95% CI = 73.8% to 94.2%), and 87.6% specific (95% CI = 84.2% to 91.1%) for delirium. When performed by physician, a RASS other than 0 was 82.0% sensitive (95% CI = 71.4% to 92.6%) and 85.1% specific (95% CI = 81.4% to 88.8%) for delirium. Using a RASS > +1 or < −1 as the cut-off, the specificity improved to approximately 99% for both raters at the expense of sensitivity; the sensitivities were 22.0% (95% CI = 10.5% to 33.5%) and 16.0% (95% CI = 5.8% to 25.2%) in the RAs and physician raters, respectively. The positive likelihood ratio was 19.6 (95% CI = 6.5 to 59.1) when performed by the RA, and 57.0 (95% CI = 7.3 to 445.9) when performed by the physician, indicating that a RASS > +1 or < −1 strongly increased the likelihood of delirium. The weighted kappa was 0.63, indicating moderate interobserver reliability. CONCLUSIONS: In older ED patients, a RASS other than 0 has very good sensitivity and specificity for delirium as diagnosed by a psychiatrist. A RASS > +1 or < −1 is nearly diagnostic for delirium given the very high positive likelihood ratio.